Pelaksanaan Terapi Aktivitas Kelompok (TAK) pada klien harga diri rendah kronis - Nofrida Saswati; Isti Harkomah; Era Rahayu; Indah Sari; Riska Asmidar; Rahmayanti Rahmayanti; Pina Lestari; Yuli Kisilowati; Adho Alif Akbar (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Clients with chronic low self-esteem are negative symptoms of schizophrenia where clients experience negative feelings about themselves and others, so that clients always feel worthless and easily despair if no intervention is carried out, it will lead to the risk of suicide. The intervention carried out in the form of Group Activity Therapy (TAK) in this activity, each group member shared experiences in overcoming problems faced related to low self-esteem. The method for this community service is in the form of simulations and Small Group Discussions where the client consists of a small group consisting of 5 people, measurements in this activity are carried out twice before being given TAK and after being given TAK using the Self-Esteem Inventory instrument from Townsend MC. The results of this community service showed a decrease in the mean value before TAK was carried out (mean 50 and after TAK) decreased to mean 45. This result indicates a decrease in symptoms of chronic low self-esteem. The results of this service are able to reduce signs and symptoms of low self-esteem, so it is recommended to nurses at the Jambi Provincial Hospital to optimize the provision of TAK to clients with chronic low self-esteem.